Pre-surgery depression and confidence to manage problems predict recovery trajectories of health and wellbeing in the first two years following colorectal cancer: results from the CREW cohort study - Foster, Claire; Haviland, Joanne; Winter, Jane; Grimmett, Chloe; Chivers Seymour, Kim; Batehup, Lynn; Calman, Lynn; Corner, Jessica; Din, Amy; Fenlon, Deborah; May, Christine M.; Richardson, Alison; et al. (Public Library of Science, 2016)
Purpose This paper identifies predictors of recovery trajectories of quality of life (QoL), health status and personal wellbeing in the two years following colorectal cancer surgery.